c - Bakar, Abu (Dhaka : Jyotiprokash, 2009)
Biography of a freedom fighter on 1971 liberation war of Bangladesh.
In Bengali.
Keywords: Bangladesh -- History -- Revolution, 1971 -- Historiography; Bengali imprints -- Bangladesh